Folding and thermodynamic studies of Trp-cage based on polarized force field - Zhang, John Z. H. (2013)
Two replica exchange molecular dynamics (REMD) simulations were carried out to study the thermodynamics of a 20-residue Trp-cage folding based on a newly developed polarized protein-specific charge (PPC). Starting from a fully extended conformation, Trp-cage native conformation was successfully sampled using REMD based on a 3-step PPC update. Next, the obtained Trp-cage folded conformation was then used to calculate the PPC in which another REMD was performed to explore the thermodynamic stability of Trp-cage. The theoretical melting temperature T m of ≈325 K was found to be in close agreement with experimental melting temperature, T m of 315 K. This indicates that the PPC was correctly predicting the temperature dependence. The current study provides a direct proof of how electrostatic polarization affects protein folding.